Flow Assurance in Petroleum Industry (International Journal of Innovative Research in Engineering & Management, 2022)
In the oil and gas business, flow assurance  is a relatively recent word. Flow assurance refers to a low cost method of producing and transporting fluids from a  reservoir to a processing facility. The growing demand of energy has led oil companies to move towards exploration in  offshore deep water sand remote places, under extreme  environmental conditions. Owing to such harsh  environmental conditions, oil companies have to face critical operational challenges during production and transportation  of crude oil. One of such menace is flow assurance issues.  Stream confirmation issues contrarily affect well  consummation plan and creation working procedures.  Hydrates, wax affidavit, naphthenates, asphaltenes,  consumption, scales, slugging, and emulsion are all stream  confirmation challenges. For stream confirmation, hydrates  and wax testimony are basic difficulties that should be  tended to first. This paper portrays the stream confirmation  challenges that impact unrefined petroleum transportation  from the repository to the retail location, both coastal and  seaward, in chilly environments. The paper also represents the process mechanism and mitigation methods used for each  fluid flow assurance issue. It is impossible to overstate the  significance of flow assurance in the oil as well as gas  business. Failure of flow assurance can result in catastrophic  consequences, such as the loss of resources or even lives.
Keywords: Asphaltenes; Flow assurance; Hydrates; Scales Wax deposition